Unsur-Unsur Intrinsik Cerpen âal-Qadiyyah al-Akhirahâ dalam Antologi Cerpen âUlbatun Min as-Safih Karya Ihsan âAbdu Al-Quddus: Analisis Struktural ROBERT STANTON - , ARIFAH FATTATIN NUR ADRIKA, Zulfa Purnamawati, S.S., M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research addresses about the intrinsic elements of âal-Qad{iyyah al Akhi>rahâ in the anthology story of âUlbatun Min as{-S{afi>h} by Ihsa>n âAbdu al Quddu>s. A structural theory is used in this short story, and using the methods of structural. The discussing points in this short story are about the intrinsic elements that contained in the short story and its interconnected elements. Intrinsic elements covered the theme of the story, the fact of the story that composed of characters, plot, setting